Influence of physical properties of carrier on the performance of dry powder inhalers - Tingting Peng; Shiqi Lin; Boyi Niu; Xinyi Wang; Ying Huang; Xuejuan Zhang; Ge Li; Xin Pan; Chuanbin Wu (Elsevier, 2016)
Dry powder inhalers (DPIs) offer distinct advantages as a means of pulmonary drug delivery and have attracted much attention in the field of pharmaceutical science. DPIs commonly contain micronized drug particles which, because of their cohesiveness and strong propensity to aggregate, have poor aerosolization performance. Thus carriers with a larger particle size are added to address this problem. However, the performance of DPIs is profoundly influenced by the physical properties of the carrier, particularly their particle size, morphology/shape and surface roughness. Because these factors are interdependent, it is difficult to completely understand how they individually influence DPI performance. The purpose of this review is to summarize and illuminate how these factors affect drug-carrier interaction and influence the performance of DPIs.